JURIDICAL REVIEW OF THE PRINCIPLE OF JUSTICE IN THE PROTECTION OF COPYRIGHT OWNERSHIP FOR WORKS CREATED IN COURSE OF PUBLIC SERVICE RELATIONS ACCORDING TO LAW NUMBER 28 OF 2014 ON COPYRIGHT DAN ITS COMPARISON WITH COPYRIGHT REGULATIONS IN FRANCE AND GERMA - Abdulghani, Muhammad Hilman; Mayana, Ranti Fauza; Muchtar, Helitha Novianty (Transnational Business Law Journal, 2024)
The regulation of copyright ownership of works created in Public Service Relations, as stated in Article 35 of the Copyright Law, indicates an injustice in the protection of copyright ownership for creators. This research aims to examine the implementation of the principle of justice in copyright ownership of works created in Public Service Relations and to compare this with the regulations in Germany and France. This study employs a comparative normative juridical approach with a descriptive-analytical research specification. Data collection is conducted through literature studies. The method of analysis used is descriptive-analytical. The results show that the regulation in Article 35 of the Copyright Law lacks elements of justice for creators in Public Service Relations. This is due to the difference in recognition given to creators of works made in Public Service Relations compared to works made in employment relationships. Compared to the regulations in Germany and France, the regulation of copyright ownership for "works made for hire" in Indonesia does not yet provide adequate protection for creators.